Peringanan Hukuman Pidana bagi Ibu yang Memiliki Anak Balita - Sani, Rafif (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This research discusses the mitigation of criminal penalties for mothers with young children, focusing on child welfare in the enforcement of law in Indonesia. In the rapidly evolving era of globalization, Indonesian law must adapt to the changing times and the continuously evolving needs of society to ensure legal certainty, justice, and utility. Legal harmonization is crucial to avoid overlapping regulations and to ensure the protection of human rights, including for vulnerable groups such as mothers with young children. The role of mothers in the development of young children is essential, and separation due to criminal penalties can negatively impact the child. Therefore, the criminal justice system should consider mitigating penalties or alternative punishments that allow mothers to remain with their children to ensure the child's welfare. This research employs a normative juridical method with a statute approach and a conceptual approach. The author also uses case studies of court decisions such as those of Angelina Patricia Pingkan Sondakh and Nita Setia Budi.